Primary non-Hodgkin's lymphomas of bone - Proulx, Gary M. (Radiology and oncology (Ljubljana), 2000)
Background. This study was performed to assess the characteristics, managementand outcome of patients with primary Non-Hodgkin's lymphoma of the bone that were diagnosed and treated at Roswell Park Cancer Institute. Patients and methods. Eighteen patients were presented to us with the criteria, for diagnosis with histopathological and immunohistochemical confirmation, of Non-Hodgkin Lymphoma with adequate bone biopsy between 1970-1996. Twelve patients received combined treatment with anthracycline based chemotherapy and localized radiation, 5 received localized radiation alone and 1 had chemotherapy alone. Results. There were fifteen patients with stage IEA, and three patients were staged IVEA. The histopathological examination revealed 13 patients with intermediate-grade diffuse, large cell, 2 patients were intermediate grade diffuse mixed small and large cells, 2 patients were intermediate grade diffuse small cleaved cell type, and 1 patient had an anaplastic large cell type. Five patients treated with combinedtreatment and one patient treated with localized radiation alone are without evidence of the disease at a median follow-up of 13 years. Six patients who had combined treatment with radiation and chemotherapy and 3 patients who had radiation alone died from progression of their disease. Two died from other causes, one with combined treatment with radiation and chemotherapy and the other with radiation alone. One patient with combined treatment was disease free at one year but was lost to follow -up. Conclusions. This study suggests that patients presenting with early-stage primary Non-Hodgkin's Lymphoma of bone can be treated with curative intent with the combination treatment of localized radiation and systemic chemotherapy. However, confirmation needs to be verified in larger and prospective studies.
Keywords: Anthracyclines; Bone neoplasms; Drug therapy; limfom; Lymphoma, non-Hodgkin's; ne-Hodkinov limfom; Pathology; Radiotherapy; rak (medicina); Therapeutic use; Treatment outcome; zdravljenje